A genome-wide association study of sprint performance in elite youth football players - Pickering, C.; Suraci, B.; Semenova, E. A.; Boulygina, E.A.; Kostryukova, E. S.; Kulemin, N. A.; Borisov, O. V.; Khabibova, S. A.; Larin, A. K.; Pavlenko, A. V.; Lyubaeva, E. V.; Popov, D. V.; et al. (The Journal of Strength and Conditioning Research, 2019)
Sprint speed is an important component of football performance, with teams often placing a high value on sprint and acceleration ability. The aim of this study was to undertake the first genome-wide association study to identify genetic variants associated with sprint test performance in elite youth football players and to further validate the obtained results in additional studies. Using micro-array data (600 K-1.14 M single nucleotide polymorphisms [SNPs]) of 1,206 subjects, we identified 12 SNPs with suggestive significance after passing replication criteria. The polymorphism rs55743914 located in the PTPRK gene was found as the most significant for 5-m sprint test (p = 7.7 × 10-7). Seven of the discovered SNPs were also associated with sprint test performance in a cohort of 126 Polish women, and 4 were associated with power athlete status in a cohort of 399 elite Russian athletes. Six SNPs were associated with muscle fiber type in a cohort of 96 Russian subjects. We also examined genotype distributions and possible associations for 16 SNPs previously linked with sprint performance. Four SNPs (AGT rs699, HSD17B14 rs7247312, IGF2 rs680, and IL6 rs1800795) were associated with sprint test performance in this cohort. In addition, the G alleles of 2 SNPs in ADRB2 (rs1042713 & rs1042714) were significantly over-represented in these players compared with British and European controls. These results suggest that there is a genetic influence on sprint test performance in footballers, and identifies some of the genetic variants that help explain this influence.